Bismuth zinc niobate pyrochlore, a relaxor-like non-ferroelectric - Rozana Aina, Maulat Osman, Dr.; Maso, Nahum; West, Anthony R. (The American Ceramic Society, 2012)
Link to publisher's homepage at http://ceramics.org/